The discovery of the orb-weaving spider genus Pinkfloydia (Araneae, Tetragnathidae) in eastern Australia with description of a new species from New South Wales and comments on the phylogeny of Nanometinae - Hormiga, Gustavo (Zootaxa, 2017)
A new species of the Australian genus Pinkfloydia, P. rixi new species, is described and illustrated. This new tetragnathid species is known only from the type locality in the eastern part of New South Wales, more than 3,200 km away from the distribution range of it sister species from Western Australia, P. harveii Dimitrov & Hormiga, 2011. The nature of such a disjunct distribution is discussed based on morphological data and on the nucleotide sequence of the mitochondrial protein-encoding gene cytochrome c oxidase subunit I. The placement of Pinkfloydia in the subfamily Nanometinae and recent advances in the phylogeny of Tetragnathidae are also discussed.